Energy‐efficient train control considering the traction system efficiency. Issue 11 (18th July 2022) - Rao, Yu; Sun, Pengfei; Wang, Qingyuan; Feng, Xiaoyun; Wang, Chuanru; Wei, Mi
Abstract: The traction system efficiency of electrical locomotive varies with the operating conditions. To minimize the mechanical energy consumption of train does not mean that the electric energy consumption is also minimum. This paper studies the energy‐efficient train control (EETC) problem considering the dynamic traction system efficiency based on the Pontryagin maximum principle (PMP) method. The authors find that the necessary optimal control modes for the problem are full power (FP), constrained partial power (CPP), coast (C), partial brake (PB), and full brake (FB). Especially, the FP‐C pair is proposed to replace the unreasonable cruising phase on the other‐non‐steep hill (ONSH). A two‐layer algorithm is designed to solve the problem and case studies are presented to illustrate the results. The influence of different train weights, different overall running times, and different kinds of traction system efficiency on the optimal driving strategy is analyzed.